Development : socio-cultural dimensions - Sharma, S. L. (Jaipur : Rawat, 1986)
Papers presented at the Seminar "Development: "Socio-cultural Dimensions" held at Dept. of Sociology, Panjab University, Chandigarh, February 15-17, 1982.
Includes bibliographical references and index.
Keywords: India -- Economic conditions -- 1947- -- Congresses; India -- Social conditions -- 1947- -- Congresses